2010
DOI: 10.1002/ldr.1069
|View full text |Cite
|
Sign up to set email alerts
|

Land degradation: socioeconomic and environmental causes and consequences in the eastern Mediterranean

Abstract: Land degradation is a natural and socioeconomic cause-effect phenomenon that is widespread all over the world. This study investigated the socioeconomic factors and causes of land degradation (e.g. population growth and urbanization, poverty, overgrazing, pollution, biodiversity, erosion) in the eastern part of the Mediterranean region. The study revealed a significant land use change from agricultural and natural vegetation to urbanized areas due to the high population increase during the last ca. 80 years (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 17 publications
1
85
1
Order By: Relevance
“…Pressure on land resources has increased dramatically because of the population growth; fallow periods between cropping cycles have been shortened from several decades to less than 1 year in the recent past. Such decline in soil fertility and productivity induced by land use change has been reported in Africa, Mediterranean regions and Asia (Biro et al, 2013;Abu Hammad and Tumeizi, 2012;Liu et al, 2014) Previous work conducted across four of the highland provinces (Southern Highlands, Eastern Highlands, Simbu and Enga) established potassium (K) deficiency as the major nutrient-related cause for the poor sweet potato productivity in almost a third of sweet potato farms Ramakrishna et al, 2009;Walter et al, 2011). These studies also reported that K deficiency was more of a problem in old farms (which have been cropped for several crop cycles) than in new farms (which are ready for cropping after fallow periods).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Pressure on land resources has increased dramatically because of the population growth; fallow periods between cropping cycles have been shortened from several decades to less than 1 year in the recent past. Such decline in soil fertility and productivity induced by land use change has been reported in Africa, Mediterranean regions and Asia (Biro et al, 2013;Abu Hammad and Tumeizi, 2012;Liu et al, 2014) Previous work conducted across four of the highland provinces (Southern Highlands, Eastern Highlands, Simbu and Enga) established potassium (K) deficiency as the major nutrient-related cause for the poor sweet potato productivity in almost a third of sweet potato farms Ramakrishna et al, 2009;Walter et al, 2011). These studies also reported that K deficiency was more of a problem in old farms (which have been cropped for several crop cycles) than in new farms (which are ready for cropping after fallow periods).…”
Section: Introductionmentioning
confidence: 75%
“…Over several years of continuous farming and in the absence of any mineral nutrient inputs, fertility of old farms generally decreases and farmers abandon such farm areas for fallow. The population of the highlands region, however, has been increasing by ∼ 3 % each year, thus placing increasing pressure on the land resources to produce extra food for the growing populace, as observed in other parts of the world (Abu Hammad and Tumeizi, 2012). Simultaneously, crop productivity appears to be declining, which has been attributed to a degradation of soil fertility linked to the progressive shortening of the fallow rejuvenation periods (Allen et al, 1995;Sem, 1996;Bourke, 2005;Walter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Along the Mediterranean coast, the problem of soil salinity is increasing due to scarcity of precipitation and irrigation with low-quality water. Saline soils here are present mainly due to human activities (Abu Hammad and Tumeizi, 2012;Domínguez-Beisiegel et al, 2013), especially with the extension of irrigation and the unmanaged use of saline water. In the Mediterranean region, 25 % of irrigated agricultural land is affected by a significant level of salinisation leading to soil degradation (Geeson et al, 2003;Mateo-Sagasta and Burke, 2011).…”
Section: S Panagea Et Al: Evaluation Of Promising Technologies Fmentioning
confidence: 99%
“…Studies on total livestock units (TLUs) in relation to stocking density consider overgrazing to occur when demand for fodder exceeds supply [18,47]. Niemeijer and Mazzucato [47] study total livestock units (TLUs) and arrive at a similar conclusion that overgrazing occurs when stocking density increases without an increase in fodder.…”
Section: Overgrazingmentioning
confidence: 99%
“…This study focuses on the depletion and degradation of land and forest resources as examples of environmental degradation. In addition to the above cited activities, overgrazing resulting from livestock stocking densities that exceed the available fodder supply is also considered to be a cause of degradation of land and forest resources [18]. Agro-pastoral systems dominate in the Sahel, and livestock numbers have increased significantly during the last 30 years in southwestern Burkina Faso [19].…”
Section: Introductionmentioning
confidence: 99%